How Age Matters in the Assessment of Vertigo in the Pediatric Emergency Department: A 10-Year Age-Stratified Etiology Survey. Issue 1 (18th September 2020) - Grasso, Antonio; Poropat, Federico; Kamagni Vodié, Theodora; Ghirardo, Sergio; Barbi, Egidio
Abstract: Vertigo is a relatively frequent cause for referral to the pediatric emergency department, and it is usually caused by benign or self-limiting etiology. However, it could be difficult to evaluate especially in the younger child and could also conceal serious illness as encephalitis or cerebellitis. Our survey collected in a 10-year period 757 children assessed in pediatric emergency department for vertigo and stratified this population for etiology and for group of age: younger than 6 years (113, 14.9%), between 7 and 12 years (251, 33.2%), and older than 12 years (393, 51.9%). In addition, associated signs and symptoms, evaluation by a neurologist or an otorhinolaryngologist, and instrumental investigations were recorded. We found that age is the most important variable to assess the possibility of a central nervous system disease as etiology cause of vertigo with a significant difference of incidence between the younger group (younger than 6 years, 23%) and older groups (3% and 1%; P < 0.001). This finding should reinforce the index of suspicion for a central nervous system illness as cause of vertigo in the preschool children with an accurate workup including evaluation by a neurologist or an otorhinolaryngologist and instrumental investigations as needed.